Complete blalock–taussig shunt obstruction in < 24 hours post‐operative period in a neonate treated emergently using transcatheter angioplasty and low dose local recombinant TPA. Issue 6 (21st November 2013) - Patange, Amit; Blake, Jennifer; Gowda, Srinath
<x xml:space="preserve">Abstract</x> A 12‐day‐old infant with pulmonary atresia, intact ventricular septum, and pulmonary blood flow through a ductus arteriosus developed complete shunt obstruction within 12 hr of creation of a modified Blalock–Taussig shunt. Low dose recombinant tissue plasminogen activator was administered locally as two 0.03 mg/kg bolus injections and was followed by balloon angioplasty. This resulted in complete recanalization of the shunt without any hemorrhagic complications. © 2013 Wiley Periodicals, Inc.